Otimização computacional da avaliação de resultados de ensaios físico-químicos em transformadores de potência - Moura, Nicolas Kemerich de (2018)
This dissertation aimed to apply several computational methods of optimization and compare their performance in the evaluation of results of physicochemical tests in power transformers. The systematic generalization of the general method of evaluation and classification – normalized doubly weighted sum –, was presented, it was improved by reducing parameters and it was applied to the physicochemical tests, which allowed the evaluation of the insulating oil of power transformers through a Global Note. The results highlighted the high adaptability of the evolutionary algorithm to this specific problem. Furthermore, the high accuracy rates obtained through optimizations explained the potential of applying the weighted sum method as a tool to aid the diagnosis of power transformers, contributing to more efficient maintenance in those devices and better monitoring of the evaluation of their operating conditions, improving the reliability of the electrical system.